The knowledge organisation of sub-subgenres: the curious case of the collaborative works of Gilbert and Sullivan - Lee, Deborah (Information Research an international electronic journal, 2025)
Introduction. This paper explores the knowledge organisation of sub-subgenres and takes a micro-level approach to genre classification. The study uses a particular case study: the classification issues around the collaborative works of Gilbert and Sullivan. Method. This paper uses literature analysis (musicological, theatrical and literary) and classification scheme analysis (informal domain classifications). It applies three classification theory ideas – characteristics of division, boundaries of classes and thesaural relationships – to the domain knowledge of Gilbert and Sullivan. Analysis/results. Novel characteristics of division are found to be at play, for creator, theatre and producer. Furthermore, issues with the porous boundary of Gilbert and Sullivan as a sub-subgenre are modelled using a Venn diagram for characteristics of division. This model highlights the lack of consistent application of characteristics on one hand and differing ideas about the outer boundaries of this sub-subgenre on the other. A study of the hierarchical, equivalence and associative relationships furthers understanding of the classification issues, especially a complex merging of hierarchical and equivalence relationships in the term Savoy opera. Conclusion. This study shows that knowledge organisation can be used to gain understanding of classifying Gilbert and Sullivan, and the value and novelty of studying sub-subgenre classification within knowledge organisation.